THE DEVELOPMENT OF SABC (SOLVE ACID BASE CASE) GAME ORIENTED ANDROID AS INTRUCTIONAL MEDIA ACID BASE FOR ELEVENTH GRADE SENIOR HIGH SCHOOL (Universitas Negeri Surabaya, 2017)
This research aims to discover the advisability of an android game called SABC (Solve Acid Base Case) as instructional media acid based for eleventh grade senior high school in term of validity, practicality and effectiveness. This research is a Research and Development Cycle type, according to Borg and Gall the steps included as: (1) Research and Information Collecting, (2) Planning, (3) Develop Preliminary of Product, and (4) Preliminary Field Testing. Assessment Instruments that used were game review sheet as media, game validation sheet, student activity observation sheet, test result sheet of student learning result and student’s questionnaire response. The SABC game reviewed by two chemistry lecturers and validated by three chemistry lecturers and one chemistry high school teacher and tested to twenty students in XI MIPA, SMAN 1 Mojosari. The result showed that the android based game Solve Acid Base Case is appropriate to be applied as an Acid Base media learning for eleventh grade High School student. From the validation assessmen, It is shown each aspect gets excellent assessment with the percentage of 82%-94% in terms of the quality of the content, the aspects of science, appearance quality, software engineering, language quality, and game requierements. Student learning shows 100% classical completeness. Result of student responses shows very good response with percentage 93.04%. Keywords: solve acid base case game, android, instructional media, acid bases